Study on tool wear and tool life during milling JFRP using uncoated carbide cutting tool - Rashid, Mohammed Abdur N.; Khan, Sher Afghan; Muhamad Khairussaleh, Nor Khairusshima; Sarifuddin, Norshahida (Asian Research Publishing Network (ARPN)., 2018)
Jute fiber-reinforcement polymer (JFRP) composite is a cheap material that is broadly used in automotive, marine, air- crafts, domestic upholstery applications because of its various high quality properties. During machining, a few of problems arise due to the Jute fiber in JFRP. Abrasive nature of this composite creates tool wear on the cutting tools during JFRP machining, thereby the life of the cutting tool become shorter and damage the surface quality. In this study, the solid uncoated carbide cutting tool (8.0 mm) performance and the life of tool were measured on the JFRP composite panel during the CNC milling process were examined. A spindle speed ranging from 671.57 rev/min to 6328.43 rev/min and a feed rate ranging from 108.58 mm/min to 391.42 mm/min were used in the experiment. Results found that the longest tool life 41.6 min were achieved at lowest feed rate 108.58 mm/min and the highest spindle speed 6328.43 rev/min effects on tool life 14.4 min. The shining area of the cutting tool shows the abrasive nature of jute fiber and chips formation mechanism.